2017
DOI: 10.21307/ijom-2017-070
|View full text |Cite
|
Sign up to set email alerts
|

The ROAM Project Part 1: Exploring new frontiers in video conferencing to expand the delivery of remote O&M services in regional Western Australia

Abstract: Twenty-five trials were conducted over a three-month period to investigate the potential for delivering O&M services remotely via video conferencing. Participants varied in age, geographical location, level of functional vision, and O&M goals. The video conferencing connection was made using the Vidyo software platform. Eleven participants (located remotely) were required to wear a chest harness that had been adapted to connect with an iPhone 6+, and were accompanied by a support person. An office-based O&M sp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 12 publications
0
4
0
Order By: Relevance
“…There are approximately 250 O&M specialists and guide dog mobility instructors in Australia and New Zealand, mostly itinerant, serving urban, rural and remote clients [15]. Dynamic videolink technologies like WhatsApp, FaceTime and the ROAM system are already used by some professionals to bridge huge distances and trouble-shoot travel challenges with clients in between visits [16,17].…”
Section: Introductionmentioning
confidence: 99%
“…There are approximately 250 O&M specialists and guide dog mobility instructors in Australia and New Zealand, mostly itinerant, serving urban, rural and remote clients [15]. Dynamic videolink technologies like WhatsApp, FaceTime and the ROAM system are already used by some professionals to bridge huge distances and trouble-shoot travel challenges with clients in between visits [16,17].…”
Section: Introductionmentioning
confidence: 99%
“…Many studies have looked at the potential of providing remote sighted guidance to people with visual impairments. The context for guidance varies from having access to visual surroundings (e.g., objects [9] and people [7]) and supporting indoor navigation [11,24,39], to remote mobility training [8,13]. For this remote guidance from sighted crowd, people with visual impairments often share their camera view either on their smartphone or smart glasses and post associated questions.…”
Section: People With Visual Impairments Remote Guidance and Asssistiv...mentioning
confidence: 99%
“…In particular, our community has provided suggestions on remote guidelines that sighted people should follow to help people with visual impairments in indoor navigation [24] and remote mobility training [8,13] when communicating via video calls. This access paradigm has long moved from research labs to real-world applications, such as BeMyEyes [17], TapTapSee [2], and Aira [3].…”
Section: People With Visual Impairments Remote Guidance and Asssistiv...mentioning
confidence: 99%
“…Prior to the pandemic, Barrett-Lennard (2016) and Battistin et al (2005) reported benefits of using DL to meet the needs of learners who live in rural and remote communities. Both research teams emphasized that the specific needs of students with disabilities must be addressed through tailoring the use of technology to meet the specific needs of any given student.…”
mentioning
confidence: 99%